Cultural intimacy : social poetics in the nation-state - Herzfeld, Michael (Routledge, 2005)
In the third edition of this important and influential book, Michael Herzfeld revisits the idea of ‘cultural intimacy’. The chapters examine a range of topics touching on the relationship between state and citizen, and the notion of ‘national character’. Herzfeld provides a developed theoretical framework and additional clarification of core concepts such as disemia, social poetics and structural nostalgia. The text has been fully updated in light of recent scholarship and events, including comment on Greece and the European Union. There is new material drawn from regions such as Thailand and China, and further consideration of religious intimacy and its impact on cities. The book improves our understanding of how states, societies and institutions function and illustrates the relevance of anthropology to contemporary issues such as globalization, censorship, ethnic conflict and nationalism.